Students’ Perception of Incorporating Moodle in an ESP Context - Đorđević, Danijela D.; Stefanovič-Kocol, Anna A. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
A Moodle platform can be successfully integrated into any course for the purpose of introducing e-learning as well as blended learning. The aim of this paper was to investigate whether students were content with having the Moodle platform as a part of the course English for Specific Purposes. The respondents were the students of the Faculty of Agriculture, University of Belgrade. The primary objective of this research was to see whether students find e-learning, and the Moodle course in particular, favourable to their learning. Furthermore, we were also eager to hear about their attitudes towards communication with other students and the teacher as well as about their preferable form and way of learning. Finally, we wanted to learn how their self-assessment correlated with their attitudes towards e-learning in order to reach some conclusions for further research.
Keywords: students’ perception; English for Specific Purposes; e-learning; Moodle